The Influence of Transformational Leadership Style and Climate Work on Employee Performance With Work Motivation as an Intervening Variable in Agency Offices Regional Disaster Management (BPDB) North Sumatra - Muhammad Haikal; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of transformational leadership and work climate on Employee Performance mediated by Work Motivation at the North Sumatra Regional Disaster Management Agency (BPDB) Office. This research was carried out at the North Sumatra Regional Disaster Management Agency (BPDB) Office. The type of research is quantitative associative. The sample in this study is 127 employees with ASN and honorary status at the North Sumatra Regional Disaster Management Agency (BPDB) Office. The sampling technique in this study uses a random sampling technique from the entire population of 186 people. The results of the study show that Transformational Leadership has a significant influence on Employee performance as shown by a T-Statistic value of 23.039 > 1.96 and a P Value of 0.000 < 0.05. In the influence of Work Climate on employee work, data on T-Statistical values were obtained from 1.251 < 1.96 and P-Value values of 0.213 < 0.05 or there was no effect of work climate on employee performance. Transformational Leadership Style has a significant effect on Employee Work Motivation with a T-Statistic value of 17.128 > 1.96 with a P-Value of 0.001 < 0.05. Work Climate has a significant effect on Employee Work Motivation. This can be seen from the results of the T-Statistic value of 67.389 > 1.96 with a P-Value of 0.000 < 0.05. On the effect of Work Motivation on Employee performance, a T-Statistic value of 19,409 < 1.96 with a P-Value of 0.000 > 0.05 which means that Work Motivation does not have a significant effect on the performance of Employees of the North Sumatra Regional Disaster Management Agency (BPDB) Office. In the indirect influence, the results show that Work Motivation has a role as an intervention variable in explaining the relationship between Transformational Leadership and Work Climate with Employee performance. This shows that improvements in Transformational Leadership and Work Climate can increase Work Motivation, which ultimately contributes to improving employee performance at the North Sumatra Regional Disaster Management Agency (BPDB) Office. Top of Form